Meta-Analysis of the Impact of International Financial Reporting Standard ( IFRS) on Financial Quality - Arifin, Andi Harmoko (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to conduct a meta-analysis of the impact of the implementation of the International Financial Reporting Standard (IFRS) on the quality of financial statements. Through the collection of data from various studies that have been conducted previously, this study integrates empirical results to obtain a more comprehensive understanding of the effects of IFRS on the transparency, accuracy, and reliability of financial statements. This study identified, assessed, and synthesized findings from 12 selected studies from the period 2022 to 2024. The results of the analysis show that the implementation of IFRS significantly improves the quality of financial statements with a Hedge's (d) value of 1,082 in the high effect size category. This effect is especially strong in countries with high levels of financial supervision and strong legal systems. These findings provide evidence to support the implementation of IFRS as an effective global standardization tool in improving the quality and reliability of financial statements internationally. The study also discusses the implications of the findings for regulators, practitioners, and users of financial statements and presents recommendations for further research.